Cost-effectiveness of HPV vaccination in Belize. (7th May 2015) - Walwyn, Leslie; Janusz, Cara Bess; Clark, Andrew David; Prieto, Elise; Waight, Eufemia; Largaespada, Natalia
Abstract: Objective : Among women in Belize, cervical cancer is both the leading cancer and the leading cause of cancer deaths. Both the quadrivalent and bivalent human papillomavirus (HPV) vaccines are licensed in Belize. The Ministry of Health of Belize convened a multidisciplinary team to estimate the costs, health benefits, and cost-effectiveness of adding an HPV vaccine to the national immunization schedule. Methodology : The CERVIVAC cost-effectiveness model (Version 1.123) was used to assess the lifetime health and economic outcomes of vaccinating one cohort of girls aged 10 years against HPV. The comparator was no HPV vaccination. The PAHO Revolving Fund negotiated price of US$ 13.79 per dose was used (for the quadrivalent vaccine) and national data sources were used to define demography, cervical cancer incidence and mortality, cervical cancer treatment costs, and vaccine delivery costs. Estimates from international agencies were used in scenario analysis. Results : In a cohort of ∼4000 Belizean girls tracked over a lifetime, HPV vaccination is estimated to prevent 69 new cases of cervical cancer (undiscounted), and 51 cervical cancer deaths (undiscounted). Considering the potential cervical cancer treatment costs and lost wages avoided by households (societal perspective), the cost per disability-adjusted life year (DALY) averted was estimated to be US$ 429. This increased to US$ 1320 when cervical cancer treatment costs and lost wages were excluded from the analysis. Both estimates are far below the gross domestic product (GDP) per capita of Belize (US$ 4795). The lifetime health care costs saved by the women and their families represent more than 60% of the investment cost needed by the Government for the vaccine. Conclusion : Routine HPV vaccination would be highly cost-effective in Belize. If affordable, efforts should be made to expedite the introduction of this vaccine into the Belizean national immunization program.